Effects of 2% Dorzolamide Hydrochloride and 0.005% Latanoprost Solutions on the Eye Surface of Rabbits - Barbosa, Elaine Baptista; Silva Junior, Paulo Gabriel Pereira; Melo, Marília Martins (Acta Scientiae Veterinariae, 2020)
Background: The glaucoma is a progressive optical neuropathy generally associated to the increase of the intraocular pressure (IOP). It is a disease of difficult therapeutic conduct and potential cause of blindness. The dorzolamide at 2% and the latanoprost at 0.005% are topical antiglaucoma drugs that cause significant reduction of the IOP. We decided to evaluate the local adverse effects of the dorzolamide at 2% and of the latanoprost at 0.005% in rabbits treated during 120 days. Materials, Methods & Results: Eighteen adult male rabbits were used in this study. They were randomly distributed into 3 groups (G) [n = 6]. Each animal received topical treatment in both eyes: GI (latanoprost at 0.005%, SID); GII (dorzolamide at 2%, TID) and GIII (ultra-pure water, TID) during 120 days. Ophthalmological evaluation was carried out through daily clinical examination, and at the end of the 120 days of treatment, it was verified clinical-ophthalmological alterations in the eyelids. The measurement of ECC was performed in triplicate, obtaining the lowest value among them as a result. They were carried out at the same time, in the morning between 9 and 10 am in order to avoid the effects of daytime ECC variation related to corneal hydration. In animals from group I, changes were observed in two eyes. Conjunctival hyperemia and ocular secretion, both in mild degree, were evidenced, respectively, in 13.75% and 9.1% of the observations. Conjunctival hyperemia was characterized from the 16th day and lasted until the final time (120 days). The animals from GII, treated with dorzolamide at 2%, presented the highest number of ophthalmological alterations. At the end of the experiment, conjunctival and eyelid changes and presence of ocular secretion, both ranging from mild to moderate, were observed in 60% and 16.32% of eyes, respectively. The animals from control group, GIII, did not present ophthalmological alterations. Discussion: Clinical signs observed in eyes treated with 0.005% latanoprost and 2% dorzolamide hydrochloride demonstrated manifestations of toxicity and / or ocular allergy. The adverse effects described may be related to the preservative of eye drops, benzalkonium chloride, a quaternary ammonia, which demonstrated ocular tissue toxicity, in vivo and in vitro. Benzalkonium chloride present in antiglacomatous drugs can cause conjunctival inflammation affecting the normal immunological functions of the eye. The presence of the preservative mainly justifies the changes found in the group of animals treated with 0.005% latanoprost, considering that the concentration of benzalkonium chloride in this drug is 0.02%, that is, two and a half times greater than of 2% dorzolamide, which is 0.008%. It should be noted that deleterious effects were associated. The other hypothesis associated with the adverse effects observed in the 2% dorzolamide treated group is related to the pH of the drug. This eye drop has a pH of 5.6, while that of 0.005% latanoprost is 6.7. This indicates that 2% dorzolamide may have secondarily induced ocular changes by virtue of its acidic pH. The association of low pH and the presence of benzalkonium chloride in concentration above 0.005% as a preservative of eye drops explains the high percentage of changes observed in this group. When facing the results, one can conclude that the treatment with the latanoprost at 0.005% and dorzolamide at 2% promoted clinical alterations to the eyelids and the conjunctive of rabbits.